The first single-incision plus one-port transverse colon resection using Senhance Digital Laparoscopy System: a case report - Yume Minagawa; Yasumitsu Hirano; Atsuko Kataoka; Satoshi Shimamura; Masahiro Kataoka; Masahiro Asari; Takatsugu Fujii; Shintaro Ishikawa; Toshimasa Ishii; Hiroshi Sato; Shinichi Sakuramoto; Kojun Okamoto; et al. (Surgical Case Reports)
Abstract Background We have introduced the Senhance Digital Laparoscopy System and actively use for colorectal cancer surgery. Recently, we also try to perform surgery by reduce port as less invasive method. For the first time, we report a case of single-incision plus one-port transverse colectomy using Senhance system. Case presentation The case was a 57-year-old woman, diagnosed with transverse colon cancer referred to our department. The preoperative diagnosis was cT1bN0M0, Stage I. We performed single-incision plus one-port transverse colon resection using Senhance system without any problems. The operative time was 203 min and the blood loss was 35 ml. Conclusion We report the first case of single-incision plus one-port transverse colectomy using Senhance system. We trust this approach will find increasing use, enabling a safer means of minimally invasive robotic surgery.